PENGARUH KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN BANK MUAMALAT CABANG SEMARANG - Suparjati, 14.05.51.0283; Murdiyanto, Agus (Students Journal of Economic and Management, 2016)
A thesis research was intended to analyze the influence of leadership on the performance employees of Bank Muamalat Semarang and analyze the influence of work motivation on the performance employees of Bank Muamalat Semarang. The population used in this research is employees of Bank Muamalat Semarang. Sample of research is a total 68 people.Â The data used in this research is primary data obtained from the result of the questionnaires distributed and secondary data obtained through the intermediary. The results analysis and discussion can be summed up as follows : leadership influential variables positive and significant on the performance employees of Bank Muamalat Semarang. It means Bank Muamalat Semarang leader have received a response either by employees in terms of his duties as chairman and granting a boost for progress employees. Variable working motivation influential positive and significant on the performance employess of Bank Muamalat Semarang. It means working motivation employees of Bank Muamalat Semarang response better if all it takes employees can be met by the company. Keywords : Leadership, work motivation, performance